Newspapers as policy actors in urban school systems: the Chicago story - Wong, Kenneth K.; Jain, Pushpam (1999)
Public schools operate within a local context where institutional actors facilitate or constrain policy decisions. The authors focus on the role of the local newspapers. In this study of news reporting on educational issues in Chicago, they apply two analytical perspectives - namely, the pluralist bargaining model and the unitary actor model. They created a database of news reports on the city's educational matters by two major Chicago newspaper for a 20-month period. Analysis suggests a strong unitary tendency in news reporting by the city's two major newspapers, as they are situated in the midst of mayor-led reform in schools. - Reproduced
Keywords: Newspapers - United States; Schools - United States; Schools